Evolución del uso de los materiales plásticos en la industria automotriz - Ramos Rivero, Virgilio Lucas (2018)
The development of the automotive industry is directly and significantly related to the use of different materials and although not all cars are the same, the materials that they are built are practically the same. The satisfaction of the requirements of a car, the costs of production, the reduction of costs related to fuel consumption, the reduction of weight and safety, are essential factors for the design and selection of the appropriate materials and their combination. Among the materials that are being used progressively and forcefully in the manufacture of automobiles are polymers or plastics, which due to their attractive properties to meet some of the requirements of different components and qualities of a car, are making a difference in some aspects in relation to other materials. This article provides succinct information about the evolution of the use of polymer or plastic materials in the automotive industry, the advantages they present in relation to other materials, their different types, their impact on the design of automobiles and other aspects of interest